Role of fecal calprotection in predicting endoscopic recurrence in postoperative Crohn's disease. (3rd October 2021) - Primas, Christian; Hopf, Gertrud; Reinisch, Sieglinde; Baumann, Lukas; Novacek, Gottfried; Reinisch, Walter; Vogelsang, Harald
Abstract: Background and aims: Fecal calprotectin (fCP) has been shown to correlate with endoscopic disease activity in Crohn's disease (CD). The aim of this study was to evaluate its role in predicting early endoscopic recurrence in postoperative CD. Methods: Patients who underwent CD-related intestinal resection with ileocolonic anastomosis were prospectively followed up until ileocolonoscopy was performed around 12 months post-surgery. Endoscopic recurrence (ER) was defined as modified Rutgeerts score i2b or higher. Endoscopic still images were reviewed by 2 independent reviewers blinded to fCP results. Stool specimens were collected 6 months post-surgery and a multivariate logistic regression model was established to explore the predictive value of fCP for ER. Results: 79 patients were included. FCP was significantly associated with endoscopic recurrence ( p = .036). A cut-off value of fCP of 267 µg/g at 6 months post-surgery predicted ER with a sensitivity of 61.8% and a specificity of 72.7% (AUC 0.669). A prediction model subsuming age at diagnosis and fCP 6 months post-surgery were significantly associated with ER (fCP at 6 months [ p = .007] and age at diagnosis [ p = .004], multivariate analysis). Conclusions: FCP 6 months after surgery and age at diagnosis predict early ER at 1 year postoperatively. However, the low sensitivity of fCP still suggests the necessity of endoscopy as a gold standard for the assessment of postoperative recurrence of CD. KEY SUMMARY: What is already known? Fecal calprotectin (fCP) correlates with endoscopic disease activity. Endoscopic recurrence occurs in up to 70% of patients after intestinal resection within 1 year. What are the significant and/or new findings of this study? Fecal calprotectin 6 months post-surgery and age at diagnosis significantly predict endoscopic recurrence at 1 year. Due to low sensitivity fCP cannot replace the necessity of endoscopy for accurate assessment of postoperative recurrence.